Observations from a georesistivimeter for time lapse analysis (G.Re.T.A.) in a closed red mud tailings storage facility - Bryson, I; Millington, L (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
The management and monitoring of closed tailings storage facilities in perpetuity requires different considerations compared to active operating facilities. At Gove, located in East Arnhem Land in the Northern Territory, Australia, red mud ponds have been capped to prevent infiltration of surface water and resaturation of the tailings. It is expected that the phreatic surface will drop over time, making the tailings less saturated, particularly in the upper portion of the facility. For this reason, traditional phreatic surface monitoring with vibrating wire piezometers (VWPs) is not fit for purpose as they are not capable of accurately monitoring unsaturated conditions and they do not always function when re-saturated after dry periods. Closed sites also typically have fewer personnel on site and restricted or limited access, which makes autonomous monitoring systems that require little to no maintenance highly desirable. To address the issue of monitoring unsaturated conditions in tailings, embankments and future cover systems, a trial of a georesistivimeter for time lapse analysis (G.Re.T.A.) instrument was conducted in the embankment of aclosed and capped red mud pond at Gove. This monitoring systemprovides a resistivity profile of the selected area to assess the evolution of the water content in the embankment and underlying tailings. The instrument was installed in July 2023 and has been providing reliable data throughout the 2023/2024 wet season. The trial embankment was selected as it is an upstream raised embankment that is well instrumented, and it has had an observed elevated phreatic surface in the past and known managed seepage. Initial observations of the data have shown a strong data correlation between the phreatic surface interpolated by G.Re.T.A. and the VWPs in the same section as well as a response to rainfall.
Keywords: tailings storage facility; post-closure monitoring; phreatic surface monitoring